Bending Characteristics of Helicoidal Laminated CFRP. (2017) - Hosome, Takayuki; Zaike, Shoichi; Matsumoto, Takashi
Abstract: The purpose of this study is to investigate if the brittle behavior of CFRP can be mitigated. A way to achieve the purpose is to follow a biological structure, so-called biomimetics. In this study, mantis shrimp is selected. The characteristic structure of its forefoot is that chitin fibers are stacked while changing spirally their angles. Three point bending tests were carried out, and load and displacement were recorded. During the tests, the specimens were observed until fracture with a video camera. Finally, bending characteristics of helicoidally laminated CFRP specimens were evaluated through comparison. It was found that the brittle behavior of CFRP could be mitigated by a helicoidally laminated structure.